Convergence analysis of environmental efficiency from the perspective of environmental regulation: evidence from China - Feng, Suling; Wu, Haoyue; Li, Guoxiang; Li, Liping; Zhou, Wenting (Technological and Economic Development of Economy, 2020)
The aim of this paper is to analyze the impact of environmental regulation on regional environmental efficiency convergence using the fixed effects model and threshold regression model. The results show that the differences in environmental efficiency have a convergence trend in China, as well as in the eastern, central and western regions. The effect of environmental regulation on regional environmental efficiency is inhibition first and then promotion, research and development investment and outward foreign direct investment have a positive transmission effect; when environmental regulation intensity exceeds a certain threshold, the growth rate of environmental efficiency in the central and western regions will be significantly higher than that in the eastern regions.